New genus and species of cockroaches from the tribe Brachycolini (Blattaria: Blaberidae: Blaberinae) and redescription of the Hormetica strumosa - Vidlička, Ľubomír (Zootaxa, 2019)
From the tribe Brachycolini Beier, 1961 new genus with one species Quadrihormetica onorei Vidlička, gen. et sp. n. and species Lucihormetica yasuniana Vidlička, sp. n. from the region Oriente (Amazon), Ecuador are described. The new genus is clearly distinguished from all other genera by specific shape of pronotum. The male of Hormetica strumosa is redescribed and illustrated; his female is the first time described.